Characterization and mapping of sensilla on the head appendages of noterid larvae (Coleoptera: Noteridae), and development of a preliminary biometric method for taxa delimitation. (31st August 2020) - Urcola, Juan I.; Benetti, Cesar J.; Alarie, Yves; Rodriguez, Georgina; Michat, Mariano C.
Abstract: Larvae of the burrowing water beetle family Noteridae are distributed worldwide and are often abundant in a broad range of aquatic habitats, playing an important role in structuring freshwater communities, yet they have remained among the most poorly studied groups of aquatic beetles. Studies on sensillar equipment of aquatic insect larvae are largely lacking, despite their potential use in phylogeny and biometric identification methods. In this article, the external morphology and distribution of sensilla on the head appendages of first instar larvae of selected genera of Noteridae were examined using scanning electron microscopy. Seven main types were distinguished based on their morphological structure: basiconica (3 subtypes), campaniformia (2 subtypes), chaetica (7 subtypes), coeloconica (6 subtypes), coniform complex (2 subtypes), placodea, and styloconica (3 subtypes). The apex of the labial palpus was found to be the most variable and informative region in regard to the number, relative position, and topology of sensilla. Fingerprint models were, therefore, generated for this region in each of the studied genera, allowing their identification. Abstract : Fingerprint models were generated based on the morphology and distribution of sensilla on the surface of the body of noterid larvae. These models allow the identification of the taxa studied, and provide characters for phylogenetic analyses. Fingerprint models generated from the sensilla of the apex of the labial palpus allow identification of the Noteridae genera studied. The study of these fingerprints provides a new set of characters useful for phylogenetic analyses.